Comparative Overall Comorbidity Burden Among Patients With Hidradenitis Suppurativa - Reddy, Sarah (JAMA Dermatol, 2019)
IMPORTANCE: The overall comorbidity burden among patients with hidradenitis suppurativa (HS) has not been systematically evaluated. OBJECTIVES: To investigate the standardized overall comorbidity burden among patients with HS and to compare it with the comorbidity burden in patients with psoriasis and a control group. DESIGN, SETTING, AND PARTICIPANTS: A cross-sectional analysis was conducted of 5306 patients with HS, 14 037 patients with psoriasis, and 1 733 810 controls identified using electronic health records data from October 1, 2013, through October 1, 2018. MAIN OUTCOME AND MEASURE: The primary outcome was the mean Charlson Comorbidity Index (CCI) score. RESULTS: Each matched cohort had 3818 patients (2789 women and 1029 men; mean [SD] age, 45.7 [15.0]). Before matching, the overall mean (SD) CCI score was highest among the psoriasis cohort (2.33 [3.13]), followed by the HS cohort (1.80 [2.79]) and control cohort (1.26 [2.35]). In matched analyses, the overall mean (SD) CCI score was highest among the HS cohort (1.95 [2.96]), followed by the psoriasis cohort (1.47 [2.43]; P < .001) and control cohort (0.95 [1.99]; P < .001) patients. A total of 516 patients with HS (13.5%) had an overall mean CCI score of 5 or greater. Mean CCI score was highest for patients with HS across all sex, race, and age groups. The most common comorbidities among patients with HS were chronic pulmonary disease (1540 [40.3%]), diabetes with chronic complications (365 [9.6%]), diabetes without chronic complications (927 [24.3%]), and mild liver disease (455 [11.9%]). Patients with HS with a CCI score of 5 or greater had 4.97 (95% CI, 1.49-16.63) times the adjusted risk of 5-year mortality compared with patients with HS with a CCI score of zero. CONCLUSIONS AND RELEVANCE: Patients with HS have a higher overall comorbidity burden compared with patients with psoriasis and a control group. A significant proportion of patients with HS have CCI scores of 5 or greater, which are associated with increased mortality. This degree of comorbidity burden may warrant multidisciplinary implementation of routine screening measures.